Investigating how errors should be flagged and worked examples structured when providing feedback to novice learners of mathematics. Issue 2 (7th February 2021) - Manson, Elisapesi; Ayres, Paul
Abstract: This study investigated the effectiveness of using a sequence of worked examples as part of the feedback cycle. Worked examples were either presented as full worked examples or partial worked examples (single-step and completion formats). In two experiments, grade 8 students completed a learning phase on a mathematics topic, which was immediately followed by a testing phase. A day later, participants were given feedback on their test papers and provided worked examples to problems where errors were made, and then re-tested. In Experiment 1 ( N = 73), studying full worked examples led to greater improvement than studying single-step worked examples. In Experiment 2 ( N = 74), full worked examples led to greater improvement than studying either single-step worked examples or completion worked examples. Furthermore, no learning differences were found when learner errors were directly flagged or otherwise. In conclusion, providing full worked examples as feedback to novice learners was helpful.